Principles of adaptive optics - Tyson, Robert K., 1948- (CRC Press, 2011)
Since the publication of the second edition of Principles of Adaptive Optics, the developments and applications in this area have increased tremendously. Observatories are now producing outstanding science through adaptive optics technology; components, such as micromachined deformable mirrors and very low noise detectors, are revolutionizing the field; and the industrial and medical arenas are harnessing the capabilities of adaptive optics tools in free-space laser communications, laser-induced fusion, and retinal imaging. Although the complexity of these applications has intensified, the principles essentially remain the same. Principles of Adaptive Optics, Third Edition offers a comprehensive guide to the systems, components, and processes of adaptive optics. It covers the principles used to extract information from beams of light and improve the performance of optical systems by correcting distortions and aberrations. Condensing the vast array of literature into one accessible source, this edition incorporates recent developments and adds many new references. It discusses how the principles are applied to astronomical imaging systems, retinal imaging, and beam propagation systems. The book logically progresses from determining the sources of aberrations to designing and analyzing systems to describing major subsystems, such as wavefront sensors, correction devices, wavefront reconstruction, and real-time controls. -- Book Description.
Keywords: Optics, Adaptive.; elektronické knihy; electronic books